Lexicographic project of phraseological dictionaries: the preceding steps for the elaboration of the work - Cruz, Thyago José (Revista Diálogos, 2022)
This article proposes a discussion about the importance of the lexicographical project in the elaboration of phraseological dictionaries, restricting, in this work, only to the previous steps for the writing of this type of lexicographical work. Considerations by Penadés Martínez (2015) and Haensch (1982) guide the discussions on the development of these stages. Four phraseographic works were selected in order to demonstrate and exemplify the possibilities of building these projects and how to arrange this information in an already written dictionary. It is hoped that the topics covered will be effective in demonstrating to interested parties the relevance that a coherent and judicious planning acquires in the lexicographical work.